Crack Growth in Hydrous Soda-Lime Silicate Glass - Waurischk, Tina; Müller, Ralf; Reinsch, Stefan; Kiefer, Philipe; Deubener, Joachim; Balzer, Robert; Behrens, Harald (Frontiers in Materials, 2020)
Stable crack growth was measured for nominal dry and water-bearing (6 wt%) soda-lime silicate glasses in double cantilever beam geometry and combined with DMA studies on the effects of dissolved water on internal friction and glass transition, respectively. In vacuum, a decreased slope of logarithmic crack growth velocity versus stress intensity factor is evident for the hydrous glass in line with an increase of beta-relaxation intensity indicating more energy dissipation during fracture. Further, inert crack growth in hydrous glass is found to be divided into sections of different slope, which indicates different water related crack propagation mechanism. In ambient air, a largely extended region II is observed for the hydrous glass, which indicates that crack growth is more sensitive to ambient water.